Natural Products and Neuroprotection - Angeloni, Cristina; Vauzour, David (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Neurodegenerative diseases, including Alzheimer's, Parkinson's, Huntington's, and amyotrophic lateral sclerosis, are the most common pathologies of the central nervous system currently without a cure. They share common molecular and cellular characteristics, including protein misfolding, mitochondrial dysfunction, glutamate toxicity, dysregulation of calcium homeostasis, oxidative stress, inflammation, and ageing, which contribute to neuronal death. Efforts to treat these diseases are often limited by their multifactorial etiology. Natural products, thanks to their multitarget activities, are considered promising alternatives for the treatment of neurodegeneration. This book deals with two different forms of natural products: extracts and isolated compounds. The study of the bioactivity of the extracts is extremely important as many studies have demonstrated the synergistic effect of the combination of different natural products. On the other hand, the investigation of the activity of specifically isolated natural products can be also important to understand their cellular and molecular mechanisms and to define the specific bioactive components in extracts or foods. This book can be considered an important contribution to knowledge of the neuroprotective effect of natural products and presents a great deal of information, related to both the benefits but also the limitations of their use in counteracting neurodegeneration.